Kebermaknaan Peran Orang Tua Bagi Pendidikan Iman Anak (Upaya Keluarga Katolik Memenuhi KHK Kanon 1136 Selama Pandemi COVID-19) - Antonius Denny Firmanto; Firminus Marianto (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2022)
Abstract: The focus of this study is to explore, initiate and identify the responsibilities and roles of Christian parents in children's education during the COVID-19 pandemic in the legal review of the Catholic Church canon 1136. The coronavirus that has hit human life indeed demands and changes all orders in human life, one of which is in the world of education. Usually, formal education of children is carried out in schools. This time, the children’s formal education of the children is carried out from their  homes using the online method. This phenomenon certainly has an impact and demands the creativity of parents in seeking education for children and  children’s creativity of children in exploring every science that is learned. The methodology used in this study is descriptive qualitative with a phenomenological and interpretive approach to the text, specifically, canon 1136. This study found that children have the right to be nurtured and educated by their parents because one form of the Catholic marriage agreement is awareness, will, responsibility and obligation in seeking and ensuring a good education for children. Education taught by people includes physical, social, cultural, moral, and religious education. Keywords: good of offspring (bonum prolis), institution of matrimony, responsible procreation Abstrak: Fokus studi ini ialah menggali, menggagas dan mengidentifikasi tanggung jawab serta peran orang tua Katolik dalam pendidikan anak selama pandemi  COVID-19 dalam tinjauan Kitab Hukum Kanonik Gereja Katolik kan.1136. Virus corona yang melanda kehidupan umat manusia memang menuntut serta mengubah segala tatanan dalam kehidupan manusia, salah satunya dalam dunia pendidikan. Biasanya, pendidikan formal anak dilaksanakan di sekolah. Kali ini, pendidikan formal anak dijalankan dari rumah masing-masing dengan metode daring/online. Fenomena ini tentunya berdampak dan menuntut kreativitas orang tua dalam mengusahakan pendidikan bagi anak dan kreativitas anak dalam mendalami setiap ilmu yang dipelajari. Metodologi yang digunakan dalam studi ini ialah deskriptif kualitatif dengan pendekatan fenomenologis dan interpretif terhadap teks secara khusus kan.1136. Studi ini menemukan bahwa anak memiliki hak agar dibina, dididik oleh orang tua sebab salah satu bentuk kesepakatan nikah suami-istri Katolik adalah kesadaran, kehendak, tanggung jawab dan kewajiban dalam mengusahakan serta memastikan pendidikan yang baik bagi anak-anak. Pendidikan yang diajarkan oleh orang meliputi pendidikan fisik, sosial, kultural, moral dan religius. Kata Kunci: kesejahteraan anak (bonum prolis), lembaga perkawinan, tanggung jawab berkeluarga